2018
DOI: 10.1186/s12917-018-1665-z
|View full text |Cite
|
Sign up to set email alerts
|

Protective immunity induced by Eimeria common antigen 14–3-3 against Eimeria tenella, Eimeria acervulina and Eimeria maxima

Abstract: BackgroundAvian coccidiosis is often caused by co-infection with several species of Eimeria worldwide. Developing a multivalent vaccine with an antigen common to multiple Eimeria species is a promising strategy for controlling clinical common co-infection of Eimeria. In the previous study, 14–3-3 was identified as one of the immunogenic common antigen in E. tenella, E. acervulina and E. maxima. The aim of the present study was to evaluate the immunogenicity and protective efficacy of Ea14–3-3 in the form of DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 59 publications
(76 reference statements)
1
31
0
2
Order By: Relevance
“…In recent years, couples of antigens of E. maxima were tested as candidate antigens for subunit or DNA vaccines and showed promising protective efficacy, such as gam56 and gam82 [ 29 ], EmMIC2 and EmMIC7 [ 30 , 31 ] and some Eimeria common antigens (e.g. GAPDH and 14-3-3) [ 8 , 32 ]. Since ROMs are involved in the invasion of apicomplexan protozoa, they were considered as new candidate antigens for developing new-generation vaccines [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, couples of antigens of E. maxima were tested as candidate antigens for subunit or DNA vaccines and showed promising protective efficacy, such as gam56 and gam82 [ 29 ], EmMIC2 and EmMIC7 [ 30 , 31 ] and some Eimeria common antigens (e.g. GAPDH and 14-3-3) [ 8 , 32 ]. Since ROMs are involved in the invasion of apicomplexan protozoa, they were considered as new candidate antigens for developing new-generation vaccines [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al [29] identified immunodominant proteins of three Eimeria species (E. tenella, E. maxima and E. acervulina), in which five groups of the protein orthologs were detected as common antigens. The E. acervulina 14-3-3 antigen was shown to induce significant immune responses and provided protection against E. tenella, E. acervulina and E. maxima infection [35]. The results of the present study added more putative, common, immunoreactive proteins to the list of crossprotective antigens, which should aid in facilitating the development of multivalent vaccines against co-infections by pathogenic Eimeria species.…”
Section: Discussionmentioning
confidence: 73%
“…In recent years, couples of antigens of E. maxima were tested as candidate antigens for subunit or DNA vaccines and showed promising protective e cacy, such as gam56 and gam82 [29], EmMIC2 and EmMIC7 [30,31] and some Eimeria common antigens (e.g. GAPDH and 14-3-3) [8,32]. Since ROMs are involved in the invasion of apicomplexan protozoa, they were considered as a new candidate antigen for developing new-generation vaccine [13,14].…”
Section: Discussionmentioning
confidence: 99%